Not a Hater, Just Keepin' It Real The Importance of Race- and Gender-Based Game Studies - Leonard, David J. (Games and Culture, 2006)
Notwithstanding the presence of extreme racialized tropes within the world of videogames, public discourses continue to focus on questions of violence, denying the impor-tance of games in maintaining the hegemonic racial order. Efforts to exclude race (andintersections with gender, nation, and sexuality) from public discussions through its era-sure and the acceptance of larger discourses of colorblindness contribute to a problematicunderstanding of video games and their significant role in contemporary social, political,economic, and cultural organization. How can one truly understand fantasy, violence,gender roles, plot, narrative, game playability, virtual realities, and the like without ex-amining race, racism, and/or racial stratification—one cannot. This article challengesgame studies scholars to move beyond simply studying games to begin to offer insightand analysis into the importance of race and racialized tropes within virtual reality andthe larger implications of racist pedagogies of video games in the advancement of Whitesupremacy.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Virtual Anti-racism: Pleasure, Catharsis, and Hope in Mafia III and Watch Dogs 2 - Leonard, David J. (Humanity & Society, 2020)
This essay examines the representation and consumption of Mafia III and Watch Dogs 2 as a site of catharsis, pleasure, and empowerment. Through not only its repre-sentation of white supremacy but its rendering of intervention and transformation as violence, Mafia III and Watch Dogs 2 offer a powerful inscription of gratification. In other words, offering both a space of oppositional gaze and a virtual reality invested in challenging gaze based in violence,Mafia IIIandWatch Dogs 2 reimagine the conventions of both video games and violence.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

“Live in Your World, Play in Ours”: Race, Video Games, and Consuming the Other - Leonard, David J. (SIMILE: Studies In Media & Information Literacy Education, 2003)
As the nascent field of computer games research and games studies develops, one rich area of study will be a semiotic analysis of the tropes, conventions, and ideological sub-texts of various games. This article examines the centrality of race and gender in the narrative, character development, and ideologies of platform video games, paying particular attention to the deployment of stereotypes, the connection between pleasure, fantasy and race, and their link to instruments of power. Video games represent a powerful instrument of hegemony, eliciting ideological consent through a spectrum of white supremacist projects.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Woke Gaming: Digital Challenges to Social Injustice - Gray, Kishonna L.; Leonard, David J. (University of Washington Press, 2018)
From #Gamergate to the daily experiences of marginalization among gamers, gaming is entangled with mainstream cultures of systematic exploitation and oppression. Whether visible in the persistent color line that shapes the production, dissemination, and legitimization of dominant stereotypes within the industry itself, or in the dehumanizing representations often found within game spaces, many video games perpetuate injustice and mirror the inequities and violence that permeate society as a whole. Drawing from the latest research and from popular games such as World of warcraft and Tomb raider, Woke gaming examines resistance to spaces of violence, discrimination, and microaggressions in gaming culture. The contributors of these essays identify strategies to detox gaming culture and orient players toward progressive ends, illustrating the power and potential of video games to become catalysts for social justice
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Replaying Empire: Racialized Violence, Insecure Frontiers, and Displaced Terror in Contemporary Video Games - Leonard, David J.; King, C. Richard (Ethnicity and Race in a Changing World, 2009)
In the wake of 9/11, US popular culture has played an important role in the manufacture of consent and the mediation of contradictions. In particular, video games have aff orded the production of interactive, narrative spaces for the reassertion of race, nation, and gender. Through a close reading of two video games, Gun and Ghost Recon Advanced Warfighter 2, we unpack the insecurities of empire and how racialized violence, colonial categories, and territorial claims work to resecure Whiteness, masculinity, and Americanness. Special attention is given to the militarization of video games and rhetorical struggles over the meaning of race and culture amid the ‘War on Terror’.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Beyond Hate: White Power and Popular Culture - King, C. Richard; Leonard, David J. (Cultural politics of media and popular culture, 2016)
Beyond Hate offers a critical ethnography of the virtual communities established and discursive networks activated through the online engagements of white separatists, white nationalists, and white supremacists with various popular cultural texts, including movies, music, television, sport, video games, and kitsch. Outlining the ways in which advocates of white power interpret popular cultural forms, and probing the emergent spaces of white power popular culture, it examines the paradoxical relationship that advocates of white supremacy have with popular culture, as they finding it to be an irresistible and repugnant reflection of social decay rooted in multiculturalism. Drawing on a range of new media sources, including websites, chat rooms, blogs and forums, this book explores the concerns expressed by advocates of white power, with regard to racial hierarchy and social order, the crisis of traditional American values, the perpetuation of liberal, feminist, elitist ideas, the degradation of the family and the fetishization of black men. What emerges is an understanding of the instruments of power in white supremacist discourses, in which a series of connections are drawn between popular culture, multiculturalism, sexual politics and state functions, all of which are seen to be working against white men. A richly illustrated study of the intersections of white power and popular culture in the contemporary U.S., and the use of use cyberspace by white supremacists as an imagined site of resistance, Beyond Hate will appeal to scholars of sociology and cultural studies with interests in race and ethnicity, popular culture and the discourses of the extreme right.
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Can the Subaltern Play and Speak or Just be Played With? - Leonard, David J. (Handbook of Research on Effective Electronic Gaming in Education, 2009)
This chapter examines and responds to the silencing, resistance to any intrusion of questions about race and racism, and overall erasure of race from the debates and broader discourse concerning video game culture. It not only provides insight into the nature and logics guiding claims of colorblindness, but also connects the ideologies and culture of denial to the broader racial discourse of post-civil rights America. Hoping to inspire debate and transformative knowledge sharing, this chapter additionally offers a textually-based racial analysis of Outlaw Volleyball as an example of the type of critical examination required to move beyond a culture that often reduces bodies and voices of people of color to objects of gaze, ridicule, and consumption while denying any sorts of criticism and questions regarding the racial meaning and texts evident within much of today’s gaming.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé